Enhanced Stability and Controllability of an Ionic Diode Based on Funnel‐Shaped Nanochannels with an Extended Critical Region. Issue 17 (1st March 2016) - Xiao, Kai; Xie, Ganhua; Zhang, Zhen; Kong, Xiang‐Yu; Liu, Qian; Li, Pei; Wen, Liping; Jiang, Lei
Abstract : The enhanced stability and controllability of an ionic diode system based on funnel‐shaped nanochannels with a much longer critical region is reported. The polarity of ion transport switching from anion/cation‐selective to ambipolar can be controlled by tuning the length and charge of the critical region. This nanofluidic structure anticipates potential applications in single‐molecule biosensing, water resource monitoring, and healthcare.